FE or not FE? A Play in Two Acts - Gary Husband; Paul Murphy; Joel Petrie (PRISM)
The play that follows is a highly experimental work in progress.  It is deliberately playful, and at times absurd, which all too often reflects the lived experiences of workers in the sector.  The narrative form is employed to examine the potential challenges of engagement in scholarship, particularly methodology, for lecturers in further education embarking on research on, in and of the sector.  The play also interrogates power dynamics in FE, its ethicality, and relationship to meaning and ownership of sectoral stories and history.  A third and final act is currently under development, and the authors hope to stage a reading of the play at the ARPCE Conference in 2020.